PERBANDINGAN HASIL BELAJAR BIOLOGI DENGAN MENGGUNAKAN METODE PROBLEM POSING DAN METODE INSIDE OUTSIDE CICRLE (IOC) PADA POKOK MATERI SISTEM PENCERNAAN KELAS XI SMA YAPIP SUNGGUMINASA GOWA - Hamansah Hamansah; Syamsiah Syamsiah (Jurnal Biotek, 2015)
Problems of this study were (1) How do the results portrayed study biology that used the Problem Posing in class XI SMA Yapip IPA_1 SungguminasaGowa on the material digestive system? (2) How the results portrayed study biology that used the Inside Outside Circle (IOC) in class XI IPA2 SMA Yapip Sungguminasa Gowa on the material digestive system? (3) Are there differences in learning outcomes biology using the method of Problem Posing Methods Inside Outside Circle (IOC) and the students of class XI and class XI IPA1 IPA 2 SMA YapipSungguminasaGowa on the material digestive system? (1) To know the description of learning outcomes biology group using the method of Problem Posing (2) To know the description of learning outcomes biology group that used the Inside Outside Circle (IOC) (3) To determine differences in learning outcomes biology between groups using the method of Problem Posing and Method of Inside Outside Circle (IOC).This type of research is experimental. The study population was all students of class XI SMA Yapip Sungguminasa Gowa 2013-2014 school year totaling 110 students, divided into three classes. Samples were taken by simple random sampling method; the experiment was elected to class XI IPA 1 as much as 31 student elected as the control class is the class XI IPA 2 as many as 31 students. The study design used is ekspereimen-control. Data collection techniques using test instruments in the form of essay amounted to 10 numbers. Techniques of data analysis was done using descriptive and inferential analysis. Previously defined significance is = 0.05. After treatment in both the experimental group and the control class descriptive statistical analysis of the results obtained by the average result of learning biology experimental group = 75 whereas the average rat study results control class = 62. The results of inferential analysis of data using t test showed that the values obtained t_hitung = 10.74 and the value of T_ (table) amounted = 2.02 in the sense that the value t_hitung> than the value of T_ (table) or (10.74> 2.02), so it can be concluded that H_O rejected and the diterima.hal H_1 shows that there is a significant difference to the learning outcomes of students in biology teaching by using the method of Problem Posing higher than students in teaching by using Method Inside Outside Cicrcle (IOC).